A stakeholder approach to corporate social responsibility, reputation and business performance. Issue 2 (1st June 2015) - Taghian, Mehdi; D'Souza, Clare; Polonsky, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to investigate business managers' assessment of stakeholders' influence on corporate social responsibility (CSR) initiatives. The key stakeholders included "employees" and "unions" as internal and "public", the "media" and the "government" as external stakeholders. The purpose was to estimate the influence of stakeholders that managers perceive as important. Moreover, the study sought to identify association between the CSR construct and corporate reputation and in turn whether this influences business performance. Design/methodology/approach – This study uses a mail survey with a random sampling of senior managers sourced from Dun & Bradstreet's Australian business database, focusing on large organizations (i.e. minimum $10 million p.a. reported sales and minimum 100 employees) as the selection criteria. A conceptual model was developed and tested using structural equation modeling. Findings – The results identified that "employees" and the "public" are perceived to be the influential stakeholder groups in CSR decision-making. There was evidence of a positive relationship between the CSR construct and reputation, which in turn influenced market share, but not profitability. Research limitations/implications – This study examined a cross-section of organizations using Dun & Bradstreet's database of Australian businesses and may not fully represent the Australian business mix. The effective response rate of 7.2 per cent appears to be low, even though it is comparable with other research in the CSR area. There may have been some self-selection by the respondents, although there were no statistically significant differences identified in the corporate characteristics of those invited to participate and those responding with usable questionnaires. Practical implications – Managers can adopt a stakeholder-influenced CSR strategy to generate strong corporate reputation to improve business performance. It is important to ensure that the interests of "employees" and "public" stakeholders are addressed within organizational strategy. Respondents were less concerned about government stakeholders and thus government involvement in organizational CSR may need to be revisited. Social implications – The major concern that emerges from these findings is the absence of the perceived importance of regulatory stakeholders on firms' CSR activities. Regulatory controls of CSR messages could reduce or eliminate inaccurate and misleading information to the public. Originality/value – The analysis explains the perceived relative influence of stakeholders on CSR decisions. It also provides an understanding of the link between organizational CSR reputation and organization's performance.